Stabilizing DNAzymes through Encapsulation in a Metal–Organic Framework. Issue 57 (17th September 2020) - Zhong, Huiye; Lo, Wei‐Shang; Man, Tiantian; Williams, Benjamin P.; Li, Dan; Chen, Sheng‐Yu; Pei, Hao; Li, Li; Tsung, Chia‐Kuang
Abstract: DNAzymes are a promising class of bioinspired catalyst; however, their structural instability limits their potential. Herein, a method to stabilize DNAzymes by encapsulating them in a metal–organic framework (MOF) host is reported. This biomimetic mineralization process makes DNAzymes active under a wider range of conditions. The concept is demonstrated by encapsulating hemin‐G‐quadruplex (Hemin‐G4) into zeolitic imidazolate framework‐90 (ZIF‐90), which indeed increases the DNAzyme's structural stability. The stabilized DNAzymes show activities in the presence of Exonuclease I, organic solvents, or high temperature. Owing to its elevated stability and heterogeneous nature, it is possible to perform catalysis under continuous‐flow conditions, and the DNAzyme can be reactivated in situ by introducing K + . Moreover, it is found that the encapsulated DNAzyme maintains its high enantiomer selectivity, demonstrated by the sulfoxidation of thioanisole to ( S )‐methyl phenyl sulfoxide. This concept of stabilizing DNAzymes expands their potential application in chemical industry. Abstract : Stabilizing DNAzymes : A method to stabilize DNAzymes by encapsulating them in a metal–organic framework (MOF) host is reported. The stabilized DNAzymes show activities in the presence of Exonuclease I, organic solvents, or high temperature. Owing to its elevated stability and heterogeneous phase, it is possible to perform catalysis under continuous‐flow conditions, and the DNAzyme can be reactivated in situ by introducing K + .